First absolute measurements of fast-ion losses in the ASDEX Upgrade tokamak. (22nd August 2017) - Rodriguez-Ramos, M; Garcia-Munoz, M; Jimenez-Ramos, M C; Lopez, J Garcia; Galdon-Quiroga, J; Sanchis-Sanchez, L; Ayllon-Guerola, J; Faitsch, M; Gonzalez-Martin, J; Hermann, A; Marne, P de; Rivero-Rodriguez, J F; et al.
Abstract: A new diagnostic technique that allows to obtain absolute fluxes of fast-ion losses measured with absolutely calibrated scintillator based fast-ion loss detectors (FILD) is presented here. First absolute fluxes of fast-ion losses have been obtained in the ASDEX Upgrade tokamak. An instrument function that includes the scintillator efficiency, collimator geometry, optical transmission and camera efficiency has been constructed. The scintillator response to deuterium ions in the relevant energy range of fast-ions has been characterized using a tandem accelerator. Absolute flux of neutral beam injection (NBI) prompt losses has been obtained in magnetohydrodynamic quiescent plasmas. The temporal evolution of the heat load measured with FILD follows that measured at the FILD entrance obtained with an Infra-Red camera looking at the FILD detector head. ASCOT simulations are in good agreement with the absolute heat load of NBI prompt losses measured with FILD.